The Study of Prolidase Level and Some Biochemical Variables in Iraqi Patients with Acromegaly - Kashash, Sara A.; Hameed , Areej Sh. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2024)
Acromegaly is a condition that results from excessive growth hormone production by the anterior pituitary gland. Prolidase (PLD) is the only known human enzyme that can hydrolyze dipeptides with an amino acid at their C terminus. Reports indicate that PLD activity serves as a marker for oxidative stress in numerous disorders such as diabetes, diabetic neuropathy, chronic liver diseases, and osteoporosis. The current study aims to estimate the values of PLD, its correlation with the rest of the parameters, and ROC in acromegaly patients. A group of 61 patients with confirmed acromegaly were collected from the National Diabetic Center, Mustansyrriah University, and 60 control groups were analyzed in the same place for the parameters of the biochemical study. Acromegalic patients had changes in the levels of biochemical markers like PLD, growth hormone, insulin-like growth factor-1, and fasting blood glucose. There was a high difference (p < 0.001) between the patient group and the healthy control group. The current study shows that PLD levels are higher in patients with acromegaly than in the healthy control group. The sensitivity and specificity for PLD were high in the patient group versus the healthy control. The PLD may be a novel biomarker of acromegaly activity, and there may be an increase in fasting blood glucose, growth hormone, and IGF-1 in acromegaly patients.